2002
DOI: 10.1177/0891243202016001005
|View full text |Cite
|
Sign up to set email alerts
|

The Only Child and Educational Opportunity for Girls in Urban China

Abstract: Using data from the authors' 1998-99 survey of 1,040 eighth graders in Wuhan, China, this study explores the differences between single-girl and single-boy families with regard to parental expectation and investment in children's education, children's own educational aspirations, and mathematics performance. The authors found that contrary to the known intrafamily discrimination against girls common among families of pre-one-child generations and still common among contemporary rural families with more than on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
142
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(160 citation statements)
references
References 18 publications
9
142
1
1
Order By: Relevance
“…The college entrance examination is extremely competitive, however, and only very limited numbers of high school graduates can be admitted to colleges or universities. 20 Therefore, we chose to classify the educational levels into four groups to fully account for those factors.…”
Section: Methodsmentioning
confidence: 99%
“…The college entrance examination is extremely competitive, however, and only very limited numbers of high school graduates can be admitted to colleges or universities. 20 Therefore, we chose to classify the educational levels into four groups to fully account for those factors.…”
Section: Methodsmentioning
confidence: 99%
“…Studies at the individual family level complement a larger body of work on the changing demographic policy on women's opportunities and aspirations. Research demonstrates a shift in parental values and perceptions through investment plans in education and engagement with their children's study (Kim et al 2016;Kim and Fong 2014;Wang and Fong 2009;Fong 2004Fong , 2002Tsui and Rich 2002). There used to be the situation where large families invested little in each child or prioritized their resources in favor of sons.…”
Section: The One-child Policy and The State's Modernisation Strategymentioning
confidence: 99%
“…In many parts of China, especially in urban China, gender differences in educational attainment are now fairly small. In a study of one large city in China, Ming Tsui and Lynne Rich (2002) found that, among single-child families, there was no gender difference in parents' educational aspirations and educational spending for their sons and daughters.…”
Section: China Contextmentioning
confidence: 99%